EFEKTIFITAS MUSIK DAN RELAKSASI AROMATERAPI LAVENDER DALAM MENURUNKAN TINGKAT KECEMASAN PASIEN DENGAN TINDAKAN PEMBEDAHAN - Buston, Erni (JURNAL MEDIA KESEHATAN, 2016)
Anxiety is the most common feeling experienced by patients that have beingbeen taken care in a hospital. They feel worried with their disease more often and whatmay happen. Anxiety will be more increasing as the patients need to undergo surgery. Toreduce this feeling, patients need to get relaxation intervention by using lavenderaromatherapy and music. This study aims to analyze the effectiveness of music andlavender aromatherapy in reducing the level of anxiety of patients undergoing surgery.The design of research is Quasi Experiment with pre-test and post-test approach and alsouses independent and independent T test. Non probability sampling with purposivesampling technique is used to determine the samples. The number of samples in eachgroup is 18 respondents. Before the use of lavender intervention, 94,4% respondentsundergo high anxiety and after the treatment, it happens to only 44.4% respondents.Meanwhile, the treatment of using music is able to reduce the level of anxiety from 94,4%respondents, before the intervention, to 33,3% respondents, after the intervention. Thestatistic test using independent T-test shows p: 0,000 to the group of lavender interventionand p: 0,000 to the group of music. This explains that there is a significant influence ofusing aromatherapy lavender and music intervention in reducing the level of anxiety ineach group. After the treatment, patients feel more relaxed. There is a significantinfluence of using aromatherapy and music in reducing the level of anxiety in patientsundergoing laparatomi surgery. It is important to include intervention of aromatherapyand music as standard operation procedure in reducing the level of anxiety in patientsundergoing laparatomi surgery.